THE FUNCTION AND ROLE OF NEEDS ANALYSIS IN ENGLISH LEARNING CURRICULUM - Nazwa Maulani Dewi; Qamariah , Zaitun (Asosiasi Dosen Muda Indonesia, 2023)
Curriculum development in education requires a comprehensive needs analysis to evaluate teachers' instructional requirements and address the needs of both teachers and subjects. The primary objective is to identify effective solutions for existing curriculum-related challenges. This study specifically focuses on analyzing the English language learning curriculum, emphasizing the role of needs analysis. The research methodology involves gathering information from existing literature and scholarly sources. By conducting a needs analysis, educators gain valuable insights into their students' specific demands and requirements. This serves as a foundation for designing instructional strategies and learning materials that cater to diverse learner needs. The needs analysis process identifies the knowledge and skills necessary for students to achieve their learning goals. It enables curriculum developers to align the curriculum content and instructional approaches with learner preferences. The curriculum is tailored to suit students' proficiency levels, ensuring a systematic progression of understanding and abilities. Needs analysis is crucial in English language learning curriculum development, emphasizing the importance of understanding student needs and customizing the curriculum accordingly. By aligning curriculum development with student needs, educators can create engaging learning experiences that optimize student outcomes. Thorough needs analysis forms the basis for effective educational programs that meet the diverse needs of learners.